2018
DOI: 10.1002/jmor.20790
|View full text |Cite
|
Sign up to set email alerts
|

Histological, histochemical, and ultrastructural investigation of the male copulatory apparatus of Haminoea navicula (Gastropoda, Cephalaspidea)

Abstract: Due to its biological and systematic importance, the morphology and function of the male copulatory apparatus of Haminoea navicula, a Cephalaspidea gastropod mollusk, was investigated by light and electron microscopy. These systems are poorly understood in haminoids, but are often used in the taxonomy of the genus. In H. navicula, the male copulatory apparatus comprises the penis within a penial sheath, a seminal duct and the prostate with two lobes. The penis is a muscular structure with a tip covered by spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Because of its taxonomic relevance, the general anatomy of the copulatory apparatus of cephalaspideans is usually mentioned in species and genus descriptions. However, histological and ultrastructural data are available only for a very limited number of species (Amorim et al, ; Kress, ; Lobo‐da‐Cunha et al, ). Deeper investigations of this apparatus are currently more interesting because it is now possible to analyze correlations between the morphofunctional features of the copulatory apparatus and species positions in more robust molecular phylogenetic trees.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of its taxonomic relevance, the general anatomy of the copulatory apparatus of cephalaspideans is usually mentioned in species and genus descriptions. However, histological and ultrastructural data are available only for a very limited number of species (Amorim et al, ; Kress, ; Lobo‐da‐Cunha et al, ). Deeper investigations of this apparatus are currently more interesting because it is now possible to analyze correlations between the morphofunctional features of the copulatory apparatus and species positions in more robust molecular phylogenetic trees.…”
Section: Discussionmentioning
confidence: 99%
“…The histological studies revealed substantial differences between the copulatory apparatus in Haminoea navicula and Haminella solitaria . In Haminoea navicula the penial sheath surrounds a muscular penis containing a penial duct, which is continuous with the seminal duct (Lobo‐da‐Cunha et al, ). In Haminella solitaria a real penis is absent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations